Evaluación del aprovechamiento de la carne ovina del cruze (Cathadin, pelibuey) en la elaboración de jamón fino, en el cantón Quevedo. - Miranda Suárez, Pedro Rogelio (2012)
The this research was carried out in the workshop of meat of the experimental farm "La Maria" belonging to the State Technical University of Quevedo, located at Km 71/2 via the junction, canton Quevedo, Los Ríos province. The main objective of this research was to take advantage of the sheep meat that our area provides us with thus giving the consumer a product made from the cruze cathadin x pelibuey sheep meat because that is currently marketed as a direct product, i.e. without any industry procedure…..